Association of Helicobacter pylori in nasal polyposis - B. Nandyal, Channabasawaraj; Shankar Naik, L. R.; L., Sahana; Bhat, Quasser R.; Naaz, Farha (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: A significant number of patients with gastro esophageal reflux disease (GERD) disease are actually infected with Helicobacter pylori, transmission of the bacteria from stomach to nose may occur. Few studies have revealed the presence of Helicobacter pylori in normal nasal mucosa, in patients with chronic rhino sinusitis and in nasal polyps but the results have been conflicting and further studies are required for its establishment. The aims and objectives of the study were to study the presence of Helicobacter Pylori in nasal polyp specimen by using non specific tests- rapid urease test, Giemsa stain and H&E stain, specific tests-immunohistochemistry and culture. Methods: 35 patients with nasal polyp were underwent endoscopic nasal polypectomy. Specimens were analyzed for presence of Helicobacter pylori by urease test, Giemsa stain, Hemotoxylin and Eosin stain, Immunohistochemistry and culture. Results: Out of 35 patients 10 patients had gastro esophageal reflux disease (GERD), in which 06 patients showed positive for urease test and Giemsa stain and 3 patients picked up by immunohistochemistry test and growth in culture media. Of which Helicobacter pylori positive cases by H&E stain showed typical hyperplastic epithelium and lymphoid aggregation. Conclusions: There exists an association between H. pylori and nasal polyps and GERD. Non-specific urease test and modified Giemsa stain were positive in considerable number of cases, but the statistical significance could not be established. Immunohistochemistry and culture can be regarded as the procedure of choice in truly positive cases infected with H. pylori along with hyperplastic epithelium in H & E stain, all with co-relative finding but require larger study to establish their association which will help in further research and treatment.